Therapeutic Nanomaterials for Neurological Diseases and Cancer Therapy - Kankai Wang (Journal of Nanomaterials, 2020)
In the recent decade, nanomedicine and nanotechnology have been broadly developed leading to a significant advancement in biomedical research as well as clinical practices. The application of several functionalized nanomaterials on the molecular and cellular levels has yielded a lot of promising progresses in various fields of regenerative medicine including disease diagnosis, combinational cell therapy, tissue engineering, and drug and gene delivery. In this review, we will summarize the recent approaches of nanoscale materials utilized in neurological diseases and cancer therapy, with highlights on the most current findings and future prospects of diverse biomedical nanomaterials for tissue regeneration, drug innovations, and the synthesis of delivery system.